The Transformation of Islamic Educational Leadership in a Multicultural Society: A Theoretical Review Based on Critical Literature - Al Hadi, Abil Fida Muhammad Qois; Muh. Nur Rochim Maksum; Intan Dian Saputri; Syahrul Adam Salleh Ibrahim; Ammar Wangyee (Multicultural Islamic Education Review, 2025)
This article aims to examine and formulate a new conceptual framework for transforming Islamic educational leadership within multicultural societies. The study is grounded in the sociocultural reality of Indonesia a nation marked by extensive cultural, ethnic, and religious diversity which demands a more inclusive, adaptive, and transformative model of leadership in Islamic education. Although prophetic values such as amanah (trustworthiness), fathanah (wisdom), shura (consultation), and ‘adl (justice) have long served as normative foundations of Islamic leadership, their implementation in educational institutions remains largely centralized and insufficiently responsive to social plurality. Utilizing a qualitative library research approach, this study analyzes primary and secondary literature published between 2020 and 2025, including contemporary leadership theories, classical Islamic texts, and recent empirical findings. The results indicate that integrating Islamic values with modern leadership theories such as transformational and distributed leadership can enhance institutional capacity to create equitable, participatory, and context-sensitive learning environments. This article proposes five key pillars for leadership transformation: responsiveness to multiculturalism, synthesis of Islamic values with modern theory, moral exemplarity, impact-based effectiveness, and convergence between prophetic ethics and strategic management. The study offers an original conceptual contribution for developing Islamic educational leadership models capable of addressing the challenges of pluralism and fostering institutions rooted in the principles of rahmatan lil ‘alamin (a mercy to all creation).